Discourse 2.0: Language and New Media - Deborah Tannen, Anna Marie Trester (Georgetown University Press, 2013)
OUR LIVES NOW, in ways we are only beginning to understand, are lived with and through electronic media: We get news on the internet, read books on Kindle, find old friends on Facebook and new loves on OKCupid and Match.com. We network on LinkedIn, and create, enhance, and share images with Instagram; we â€œtweet,â€ â€œfriend,â€ and â€œfollowâ€; â€œpost,â€ â€œpinâ€ and â€œlikeâ€; and sometimes â€œ#fail.â€ As we seek to understand these new ways of using language in our lives, the new worlds of words they entail in turn provide new means of understanding who we are and how we connect through language. The chapters in this volume are drawn from the sixty-third annual meeting of the Georgetown University Round Table on Languages and Linguistics (GURT), â€œDiscourse 2.0: Language and New Media,â€ which is also the title of this volume. Included here are the five plenary addresses as well as selected papers by workshop leaders, panel organizers, and paper presenters, all of whom turn the attention of discourse analysis, broadly defined, to emerging and rapidly evolving new media platforms for interpersonal interaction. In this introduction we suggest some connections among the chapters as well as some focal themes of the volume. In chapter 1, Susan Herring sets the stage for the volume by defining and describing Web 2.0, placing it in the historical context of computer-mediated discourse analysis (CMDA) and showing that it can be understood through the lens of the tripartite classification suggested in her title, â€œDiscourse in Web 2.0: Familiar, Reconfigured, and Emergent.â€ Considering a wealth of data sources such as Second Life, YouTube, Twitter, wikis, games, Skype, and texting, she outlines her CMDA toolkit, providing a set of methods grounded in discourse analysis, which may be used to uncover patterns of structure and meaning in networked communications. The chapters that follow begin to provide the range of research that Herring calls for in her conclusion. In chapter 2, â€œPolities and Politics of Ongoing Assessments: Evidence from Video-Gaming and Blogging,â€ HervÃ© Varenne, Gillian â€œGusâ€ Andrews, Aaron Chia-Yuan Hung, and Sarah Wessler develop and integrate the notion of â€œassessmentâ€ from the disparate fields of education, mental health, and conversation analysis, by exploring three examples of the phenomenon as played out in electronic discourse: first, an interaction at a video-game design camp in which an expert child takes over the controls from an incompetent adult; next, a group of four young Chinese friends playing video games in New York City, wherein three of the young men were expert, but the fourth, a young woman, was a novice; and, finally, a series of multiparty exchanges in which a number of people mistakenly tried to cancel AOL This accounts by posting messages to the blog of an individual who had written humorously about difficulties encountered when attempting to cancel an AOL account. In all of these contexts, the authors examine the linguistic means by which incompetence or expertise is assessed by participants in the interactions, considering how such â€œindexical propositions and their interpretationâ€ are shaped by synchronicity (in faceto- face encounters), or in the asynchronicity exemplified in the blog data.